2019
DOI: 10.3390/molecules24234412
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Stilbenes and Canthinone Alkaloids from Brucea antidysenterica (Simaroubaceae)

Abstract: A phytochemical study of the root and bark of Brucea antidysenterica J. F. Mill. (Simaroubaceae) afforded three new compounds, including a stilbene glycoside bruceanoside A (1), and two canthinone alkaloids bruceacanthinones A (3) and B (4), along with ten known secondary metabolites, rhaponticin (2), 1,11-dimethoxycanthin-6-one (5), canthin-6-one (6), 1-methoxycanthin-6-one (7), 2-methoxycanthin-6-one (8), 2-hydroxy-1,11-dimethoxycanthin-6-one (9), β-carboline-1-propionic acid (10), cleomiscosin C (11), cleom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…C6 and C7 were reported for their cytotoxicity, anti-inflammatory, and antivirus activities (Ohmoto and Koike, 1988;Han et al, 2001;Chen et al, 2009b;Lee et al, 2009;Liu P. et al, 2019); their antibacterial activity is reported here for the first time. C8 showed anticancer, antimalarial, anti-inflammatory, antidiabetic, anti-plasmodium, antiprotozoal, antibacterial, antifungal, and antivirus activities (Lagoutte et al, 2008;Ross et al, 2008;Almeida et al, 2011;Arias et al, 2011;Cebrian-Torrejon et al, 2011;Agrawal et al, 2013;Rashed et al, 2013;Amanulla et al, 2017;Cho et al, 2018;Makong et al, 2019); it was active against S. aureus (of inhibition zone diameter of 6.1 mm), but no activity against E. coli was observed (Casciaro et al, 2019), which is the same as our result. C9 showed cytotoxicity against HepG2 and 3B cells, but there are no reports thus far about its antimicrobial activity.…”
Section: Bioactivity Discussion Of Kumu Compoundssupporting
confidence: 90%
“…C6 and C7 were reported for their cytotoxicity, anti-inflammatory, and antivirus activities (Ohmoto and Koike, 1988;Han et al, 2001;Chen et al, 2009b;Lee et al, 2009;Liu P. et al, 2019); their antibacterial activity is reported here for the first time. C8 showed anticancer, antimalarial, anti-inflammatory, antidiabetic, anti-plasmodium, antiprotozoal, antibacterial, antifungal, and antivirus activities (Lagoutte et al, 2008;Ross et al, 2008;Almeida et al, 2011;Arias et al, 2011;Cebrian-Torrejon et al, 2011;Agrawal et al, 2013;Rashed et al, 2013;Amanulla et al, 2017;Cho et al, 2018;Makong et al, 2019); it was active against S. aureus (of inhibition zone diameter of 6.1 mm), but no activity against E. coli was observed (Casciaro et al, 2019), which is the same as our result. C9 showed cytotoxicity against HepG2 and 3B cells, but there are no reports thus far about its antimicrobial activity.…”
Section: Bioactivity Discussion Of Kumu Compoundssupporting
confidence: 90%
“…Brucea antidysenterica is traditionally used to treat cancer, dysentery, malaria, diarrhea, stomach aches, helminthic infections, fever, and asthma [ 27 – 29 ]. Its root and bark extracts earlier displayed the cytotoxic effects against PC-3 (prostate), A-549 (lung), and MCF-7 (breast) cancer cell lines [ 30 ]. However, the present study reports for the first time the antiproliferative activities of this plant on various models of drug-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed lignans, 1-4, possessing weak cytotoxic activity with IC 50 values ranging from 32.61-95.18 µg/mL. The results agreed to published researches on cytotoxic activity of (+)-aptosimon (1, IC 50 >10 µg/mL for MCF7) [15], (+)-isolariciresinol (2, IC 50 > 100 µg/mL for KB, MCF7, HepG2, and Lu) [16], (-)-cleomiscosin A (3, IC 50 = 132 ± 112 µg/mL) and (-)-cleomiscosin C (4, IC 50 > 250 µg/mL) for MCF7) [17].…”
Section: Resultsmentioning
confidence: 99%